Astaxanthin Prevents Mitochondrial Impairment Induced by Isoproterenol in Isolated Rat Heart Mitochondria - Olga Krestinina; Yulia Baburina; Roman Krestinin; Irina Odinokova; Irina Fadeeva; Linda Sotnikova (MDPI AG, 2020)
Mitochondria are considered to be a power station of the cell. It is known that they play a major role in both normal and pathological heart function. Alterations in mitochondrial bioenergetics are one of the main causes of the origin and progression of heart failure since they have an inhibitory effect on the activity of respiratory complexes in the inner mitochondrial membrane. Astaxanthin (AST) is a xanthophyll carotenoid of mainly marine origin. It has both lipophilic and hydrophilic properties and may prevent mitochondrial dysfunction by permeating the cell membrane and co-localizing within mitochondria. The carotenoid suppresses oxidative stress-induced mitochondrial dysfunction and the development of diseases. In the present study, it was found that the preliminary oral administration of AST upregulated the activity of respiratory chain complexes and ATP synthase and the level of their main subunits, thereby improving the respiration of rat heart mitochondria (RHM) in the heart injured by isoproterenol (ISO). AST decreased the level of cyclophilin D (CyP-D) and increased the level of adenine nucleotide translocase (ANT) in this condition. It was concluded that AST could be considered as a potential mitochondrial-targeted agent in the therapy of pathological conditions associated with oxidative damage and mitochondrial dysfunction. AST, as a dietary supplement, has a potential in the prevention of cardiovascular diseases.